Rejets d’abattoir et qualité de l’eau : la rivière Yilia, Guinée - Keita, Nouhan; Tenkiano, Nathalie Sia Doumbou (European Scientific Journal, ESJ, 2026)
La qualité de l’eau des rivières est fortement influencée par les rejets industriels et domestiques, notamment ceux des abattoirs. Cette étude évalue l’impact des rejets de l’abattoir communal sur la qualité des eaux de la rivière Yilia, à N’Zérékoré (Guinée). Des échantillons ont été prélevés en amont (STA) et en aval (SAV) et analysés pour les paramètres physico-chimiques et microbiologiques, tandis que les déchets solides et liquides ont été quantifiés par enquêtes et mesures directes. Les résultats montrent une dégradation significative en aval, avec turbidité élevée (57,6 ± 21,8 NTU), matières en suspension importantes (400 ± 50 mg/L) et contamination bactérienne (coliformes fécaux : 33,9 ± 4,9 UFC/100 mL). L’abattoir produit 1,4 t de déchets solides/semi-solides et 1 458 L d’effluents liquides, déversés sans traitement. Les différences entre stations sont significatives (p < 0,05). Ces résultats confirment l’impact négatif des rejets sur la qualité de l’eau et soulignent la nécessité de stratégies de gestion durable des déchets et effluents pour protéger cet écosystème et la santé publique. Pollution of surface waters by slaughterhouse effluents represents a major environmental and public health concern in many sub-Saharan African cities. This study assesses the impact of discharges from the municipal slaughterhouse on the water quality of the Yilia River in N’Zérékoré, Guinea. Water samples were collected upstream (STA) and downstream (SAV) of the discharge point and analyzed using standardized methods (APHA, AFNOR) for physicochemical parameters (pH, temperature, turbidity, electrical conductivity, total dissolved solids, suspended solids, nitrates and nitrites) and microbiological indicators (total and fecal coliforms). In parallel, slaughterhouse waste was characterized and quantified through field observations, surveys and direct measurements. The results indicate a significant deterioration of water quality downstream of the slaughterhouse. The SAV station showed high turbidity (57.6 ± 21.8 NTU), elevated suspended solids (400 ± 50 mg/L), increased mineralization, and marked bacterial contamination (fecal coliforms: 33.9 ± 4.9 CFU/100 mL) compared with the upstream station. The slaughterhouse generates on average 1.4 tons of solid and semi-solid waste per day and approximately 1,458 L of liquid effluents, most of which are discharged directly into the environment without prior treatment. Statistical analyses confirmed significant differences between upstream and downstream stations for most parameters (p < 0.05). These findings demonstrate the negative impact of slaughterhouse effluents on the physicochemical and microbiological quality of the Yilia River and highlight the urgent need to implement appropriate waste and effluent management systems in order to protect aquatic ecosystems and reduce health risks for local populations.